Ars conjectandi three hundred years on. Issue 3 (20th June 2013) - Edwards, Anthony
Abstract : This year sees the 300th anniversary of Bernoulli's Ars conjectandi – The Art of Conjecturing . It transformed gamblers' "expectations" into modern mathematical probabilities. More importantly, it sets forth what Bernoulli called his "golden theorem"– the law of large numbers – which underpins the whole of statistical inference. Professor Anthony Edwards digs deep.